APPLICATION OF DIVERSION PENAL MEDIATION ON SEXUAL VIOLENCE CASES TO REALIZE CHILD PROTECTION FOR VICTIMS OF SEXUAL VIOLENCE - Setya Wahyudi; A Angkasa (Faculty of Law, Universitas Jenderal Soedirman, 2018)
Diversion is the granting of the authority of law enforcers to transfer the settlement of Child cases from the criminal justice process to the criminal justice process, with the aim of achieving peace between the victim and the child who commits a crime. This research is to find out about: how to apply diversion to cases of sexual violence against children, and whether diversion penal mediation can be applied to cases of sexual violence to realize the protection of children victims of sexual violence. Based on research in Central Java, barriers to the application of diversion system are from legislative factors, structural factors as well as community legal cultural factors. Along with the application of reasoning mediation diversion, these obstacles can be avoided. The application of the diversion penal mediation as a means to protect children of perpetrators and children of victims of child sexual violence. In the future there needs to be a willingness and courage for child law enforcers, to apply the diversion penal mediation to cases of child sexual violence Keyword: diversion, penal mediation, sexual violence